Reflective Practice About Retroperitoneal Laparoscopy in Comparison to Open Surgery for Ureteropelvic Junction Obstruction Repair in Children Less Than 1 Year of Age - Kallas-Chemaly, Anthony; Peycelon, Matthieu; Ali, Liza; Grapin-Dagorno, Christine; Carricaburu, Elisabeth; Philippe-Chomette, Pascale; Enezian, Goharig; Paye-Jaouen, Annabel; El-Ghoneimi, Alaa (Frontiers in Pediatrics, 2019)
Introduction: The interest of laparoscopy in the treatment of ureteropelvic junction obstruction (UPJO) in children under twelve months of age remains controversial. The aim of this study is to evaluate feasibility and benefits of retroperitoneal laparoscopy (RL) compared to open surgery in this age group. Materials and Methods: Between January 2012 and May 2017, we performed 222 pyeloplasties: 144 by laparoscopy and 78 by open surgery. From 2012, the choice of operative technique was decided according to the laparoscopic experience of the surgeon; two surgeons operated laparoscopically on all children less than 12 months of age, while others operated using posterior lumbotomy (PL). The RL is standardized and performed by 3 trocars (5, 3, 3). Pre, per and postoperative parameters were analyzed retrospectively. Statistical tests: Pearson, Fisher, Student and Mann-Whitney. Results: During this 5-year period, 24 RL and 53 PL were included with a median follow-up of 27 months (5-63). In the LR group, postoperative drainage was performed by JJ (13 cases) and external stent (11 cases). No conversion has been listed in this group. In each group there was one failure that needed redo pyeloplasty. Duration of hospitalization and intravenous acetaminophen use were significantly lower in the RL group (2.8 days vs. 2.3 days, p = 0.02 respectively) while operating time was significantly longer (163 min vs. 85.8 min, p = 0.001). The postoperative complication rate was statistically identical in each group (urinary tract infection, wall hematoma, hematuria ...). Conclusion: RL is feasible in children under one year of age in the hands of well experienced surgeons with longer operative time but without added morbidity. Subject to the retrospective nature of our study, the RL seems to offer a benefit regarding duration of hospitalization and analgesics consumption.